A Node Routing Problem with Intermediate Facilities: A Managerial Approach Based on a Heuristic Algorithm - Nafezi, Nima (2013)
In this dissertation, we discussed a type of vehicle routing problem called vehicle routing problem with intermediate facilities with consideration of the impact of adding intermediate facilities to the problem. To study how IFs change the result of the problem, we firstly present a simple model based on clustering algorithm along with finding the shortest route between clusters, implementing Clarke and Wright’s algorithm within each cluster. Then we determine a set of design of experiments which allows us to study different characteristics of the problem. Generating graphs and tables from the results, we analyse them by considering two concepts; radial routing and local routing distances. The outcomes show the more important role of radial routing distance which has often significantly higher impact compared to the local routing distance.